ANALISI FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT KONSUMEN MEMBELI PRODUK MOBIL DAIHATSU XENIA 1000CC PADA PT. ASTRA DAIHATSU PEKANBARU - Endi Trio Putra; Mariaty Mariaty (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
Abstract: problem in this research was not the realization of Daihatsu Xenia 1000cc car sales is not expanded feet according to the target diingin companies. The fokusan company in promoting car type Xenia 1000cc car type compared to the Xenia 1.3 cc. basically the car Daihatsu Xenia products include the preferred consumer kateogori and quite attractive car capable payload capacity, contains 7 to 8 persons car so this passenger. enough demand by consumers who already have a family.As for the purpose of this research is to know the factors that affect the consumer interest in buying car Daihatsu Xenia 1000 cc. site selection research at PT Astra Daihatsu Pekanbaru Sudirman Street, the sample used is 50 by using the dwarf accidental sampling.The results showed that of the four factors that are considered influential writer on car buying consumer interest Xenia 1000cc shows results approved by the respondent. There are only a few indicators according to the respondents disagree because respondents have multiple sockets, which are expressed in the deliberations of the research.Kata Kunci : product, price, promotion, life stayle